The Use Of Whatsapp Messaging As One Of Mobile Learning On Students’ Writing Skill Error - Alfitriani Siregar; Miss Rohani Pooteh; Idris Eal Al Amini; Putri Isnin Suryaningsih Hia (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The purpose of the study was to analyze the use of WhatsApp messaging as one of mobile learning on students' errors in writing recount texts with the theme "COVID 19" at SMP Negeri 4 Satu Atap Kuala, Indonesia. This research conducted Junior High School as population of 108 students in the eighth grade. Sample taken use random sampling, reduced of 27 students. The research method used is descriptive-quantitative method. Results showed that four types of writing errors are omissions, additions, misinformation, and sequence errors. The most common types of errors in writing recount text are omission errors of 3.5% and addition errors of 1%. Misinformation with 88.5% errors. And the last ordering error with 7% error. By doing this research, it is hoped that students can practice more and improve their writing skills, especially in recount texts.